Between Humanitarian Assistance and Externalizing of EU Borders: The EU-Turkey Deal and Refugee Related Organizations in Turkey. (March 2023) - Pries, Ludger; Zülfikar Savci, Berna Safak
This paper examines whether multilevel transnational cooperation makes a difference in refugee protection, especially in protracted displacement. In response to the forced migration of millions of Syrians to Turkey starting in 2011, the EU and Turkish government published a joint statement in March 2016. The so-called EU-Turkey deal (EUTD) provided a substantial flow of money (EUR 6 billion in four years) from the EU to Turkey. In return Turkey had to commit to contain and control migration movement toward the EU. In social science, there are quite diverse evaluations of the EUTD. Whereas some studies focus on its effectiveness and efficiency in reaching the outlined goals, other publications stress its geo-political effects on migrants' mobility and (externalized) border control. Meanwhile some studies look for points to improve the EUTD while others criticize it fundamentally. This article analyzes the involvement of different types of international governmental and non-governmental organizations (IGOs and INGOs) in the four main action fields of the EUTD and its implicit side effects on the Turkish regime of migration management. It first summarizes some crucial findings and pending questions in the social science literature. Based on analysis of available documents and our own interviews in Turkey, we then shed light on the organizations involved in the implementation of the EUTD and its effects on the Turkish regime of refugee protection. In 2022, Turkey hosted some 3.7 million Syrian refugees of a total of almost four million registered international forced migrants. The EUTD of 2016 was mainly a response by the EU to the large numbers of Syrian refugees arriving in its members' territories. When more than 1.2 million asylum seekers were registered in the then EU-28 in 2015 alone — more than twice the number in the preceding year — some EU member states (MS) negotiated with the Turkish government (Eurostat 2015, 2016). Based on a meeting of the European Council and its "Turkish counterpart" the so-called "EU-Turkey statement" was published on March 18 in 2015 (European Council 2016). From the very beginning, this EUTD was controversial — both in public discussions and in the social science literature. Was it primarily a payment from the EU to the Turkish government for externalizing its responsibilities of refugee protection? Or was it an appropriate measure for sharing the burden of an urgent humanitarian crisis? Was the money spent for refugee-oriented humanitarian aid and development expenses or was it instrumentalized by the Turkish government for its own ends? How did refugee related IGOs and INGOs participate in the management of the EUTD? In the following sections, we focus on some selected aspects of the role of national and international, governmental and non-governmental organizations active in the field of refugee protection, specifically the role and cooperation dynamics of these refugee related organizations (RRO) in implementing the Facility for Refugees in Turkey (FRIT) as part of the EUTD. Based on expert interviews in Turkey and an analysis of spending under the EUTD, the paper analyzes (1) how the landscape of RROs developed in the context of the EUTD, (2) how the budget of the EUTD was spent, and (3) how the cooperation between these RROs developed. The paper adds new insights into the contradictory dynamics between organizing services for refugees and controlling and containing refugee movements to the EU, between assisting and instrumentalizing forced migrants in Turkey, and between humanitarian aid and development activities. Especially the last point is relevant for contexts of protracted displacement as instruments of immediate humanitarian assistance have to be combined with means of longer-term development. From a perspective of organizational sociology, it argues that the EUTD contributed to a multi-level transnational organizational field of refugee protection, where collective and corporate actors relate in conflict and cooperation between the poles of rational self-interests and mutually recognized norms, between control-oriented state authorities up to grass root action networks. Analysis of the EUTD enables us to draw out specific insights and practical lessons for a broader audience. Before presenting our own empirical findings we first will sketch out the broader landscape of social science research and analysis of the EUTD. 2